(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study aims to shed light on the importance of controlling the marine environment, and the state’s ability to apply relevant environmental laws, given that the marine environment is an arena for many activities that may cause its deterioration or limit its exploitation, in accordance with Law No. (15) of 2003 m, for the protection and improvement of the environment, It is known that the prevention of pollution, limiting the various damages resulting from it, and combating it is a goal that most countries seek to achieve. Therefore, the study aims to focus on the appropriate methods for measuring pollution, determining its levels, and knowing whether it has an impact on the environmental balance, and the natural environment of the environment. The marine, as well as the development of plans and scientific programs in order to achieve sustainable development, and to benefit from natural resources, and to make optimal use of them.